Testosterone induces up-regulation of mitochondrial gene expression in murine C2C12 skeletal muscle cells accompanied by an increase of nuclear respiratory factor-1 and its downstream effectors - Pronsato, Lucía (2020)
The reduction in muscle mass and strength with age, sarcopenia, is a prevalent condition among the elderly, linked to skeletal muscle dysfunction and cell apoptosis. We demonstrated that testosterone protects against H2O2-induced apoptosis in C2C12 muscle cells. Here, we analyzed the effect of testosterone on mitochondrial gene expression in C2C12 skeletal muscle cells. We found that testosterone increases mRNA expression of genes encoded by mitochondrial DNA, such as NADPH dehydrogenase subunit 1 (ND1), subunit 4 (ND4), cytochrome b (CytB), cytochrome c oxidase subunit 1 (Cox1) and subunit 2 (Cox2) in C2C12. Additionally, the hormone induced the expression of the nuclear respiratory factors 1 and 2 (Nrf-1 and Nrf-2), the mitochondrial transcription factors A (Tfam) and B2 (TFB2M), and the optic atrophy 1 (OPA1). The simultaneous treatment with testosterone and the androgen receptor antagonist, Flutamide, reduced these effects. H2O2-oxidative stress induced treatment, significantly decreased mitochondrial gene expression. Computational analysis revealed that mitochondrial DNA contains specific sequences, which the androgen receptor could recognize and bind, probably taking place a direct regulation of mitochondrial transcription by the receptor. These findings indicate that androgen plays an important role in the regulation of mitochondrial transcription and biogenesis in skeletal muscle.